Renascent Empire? The House of Braganza and the Quest for Stability in Portuguese Monsoon Asia, ca. 1640-1683 - Ames, Glenn J. (Amsterdam University Press, 2000)
Based on extensive archival research in Portugal, India, England, and France, this work provides the first monographic study of a crucial, yet hitherto ignored period in the history of Portugal's Asian empire: the years ca. 1640-1683. Ames' revisionist work demonstrates that, contrary to the tradition-al view of the inevitable decline and stagnation of the Estado da India after ca. 1640, these were years of innovative and dynamic reform which brought about the geo-political and economic stabilization of Portuguese Asia by 1683. The book details this fundamental shift in Crown policy toward Asia as initiated by Prince Regent Pedro of Braganza (1668-1702) and carried out most effectively by Viceroy Luis de MedonHa Furtado e Albuquerque. This title is available in the OAPEN Library - http://www.oapen.org.